Post-traumatic parenting : break the cycle and become the parent you always wanted to be - Koslowitz, Robyn (Broadleaf Books, 2025)
""I want to parent differently than the way I was parented; I know what not to do, but I'm not so sure about what I should do." Every good parent wants to create relationships with their children that are filled with joy, connection, and healthy attachment. Yet well-meaning but traumatized parents--those who suffered as children or who are dealing with traumatic events as adults--tend to see the world from a survival point of view. If that's you, you might suspect that your own trauma is negatively influencing your parenting behaviors. Where can you turn for support and wisdom? Post-Traumatic Parenting goes far beyond the fad social-media trends like "gentle" and "responsive" parenting to provide a clear, easy-to-follow, and substantive guide, offering both what to do and why it works, so traumatized parents can create the kind of relationship they want with their children of any age. In this book, you'll learn how to properly adjust your techniques and strategies, act in accordance with your defined parenting values, and, best of all, create your own survival strategies and flip them into your parenting superpower. Experienced, renowned traumatic parenting expert, workshop leader, speaker, and founder of the Center for Psychological Growth, a large children's therapeutic practice in New Jersey, child psychologist Dr. Robyn Koslowitz directly explains exactly how every post-traumatic parent can reverse the damage from their own traumas and forge a strong, healthy relationship with their children. Finally, you can find true joy in the day-to-day of parenting. It's time to recognize that post-traumatic parenting is a deep, authentic, powerful healing journey. It features easy-to-follow instructions, along with simple tools, to help you effectively parent your children, no matter what happened in the past. Let Post-Traumatic Parenting help you break the cycle, enjoy the journey, and create healthy, joyful, dynamic, lasting relationships with your children. It is a singular guide to becoming the parent you always wanted to be."--Publisher.